2014
DOI: 10.1016/s1473-3099(14)70022-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of multidrug-resistant tuberculosis in the UK: a cross-sectional molecular and epidemiological study of clustering and contact tracing

Abstract: Public Health England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 26 publications
5
58
2
Order By: Relevance
“…Helping them understand their risk will sensitize them to cardiovascular prevention. This method is called contact tracing, which is used in infectious disease control [93]. …”
Section: Discussionmentioning
confidence: 99%
“…Helping them understand their risk will sensitize them to cardiovascular prevention. This method is called contact tracing, which is used in infectious disease control [93]. …”
Section: Discussionmentioning
confidence: 99%
“…1 However, the high risk of MDR-TB among patients with previous treatment history has resulted in a common brief that most MDR-TB cases were due to the acquisition of resistance, and led to the allocation of resources to improve treatment. Although previous studies suggested that many MDR-TB cases resulted from the transmission of MDR strains, 10-13 few studies present data that provide direct evidence of MDR-TB transmission at the population level. Thus, we hypothesized that the transmission of MDR strains plays a major role in the high prevalence of MDR-TB in China.…”
Section: Introductionmentioning
confidence: 96%
“…For example, TB models might find that the comparative impact of Xpert scale-up strategies depends strongly on the amount of ongoing TB transmission in a community, which in many places may not be known. 6 These results could motivate further data-gathering activities (e.g., molecular epidemiological characterization of acommunity, 39,40 or synthesis of existing programmatic data on TB incidence 41 ) that could help to improve decision-making related to Xpert scale-up in the future. For the spread of rubella, modelling has already led to the collection of new missing data.…”
Section: Linking Model Results To Public Health Policy Around Infementioning
confidence: 99%